ERGONOMIC REVIEW IMPLEMENTATION OF MATERIALS AND CORRIDOR FLOOR FLOOR Dr. SARJITO · YOGYAKARTA - Dwi Retno Sri Ambarwati; Eni Puji Astuti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
The aim of this research is to describe how far is the ergonomics conditions have been applied in the applying of material and colour of the corridor floor at RSVP Dr. Sarjito Yogyakarta, identifying problems that happened and also its cause.The approach of this research is descriptive qualitative, depicting what the existence of the circumstance of corridor floor at RSVP Dr. Sarjito Yogyakarta through observation and documentation 'and to describe the situation of research object, perceiving problems that happened and its cause.The result of this research indicate that the floor materialthat isapplied is ceramic tile that is equal to 99.81 %, rubber vynil is equal to0.08% and cement plaster is equal to 0.106% from entire corridor floor that becoming the research object. Colour of the floor is white that combined by old grey textured ceramic tile. Evaluated from the ergonomics conditions including the security, safety and comfort aspect, ceramic floor that used at the corridor of RSVPDR.SARJITO havefulfilled the conditions. The esthetic conditions with theprincipal consideration of composition not yet beenfullfiled because there an; no variation ofform, colour and motive. Motive, form and colour are monoton and also there are no emphasis that will attract the attention, make thefeeling bored especially whenfringing at a long corridor,so that the distancefelt farther.